PROBLEMS OF DEVELOPING COMMUNICATIVE COMPETENCE THROUGH MOBILE APPLICATIONS IN THE EDUCATIONAL PROCESS - Fayzulloyevna, Norova Fazilat (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze the development of students’ communicative competence through the use of mobile applications in the educational process. Method: A descriptive and analytical approach was applied to evaluate the pedagogical potential of mobile platforms such as Duolingo, Google Classroom, Kahoot, and Telegram, focusing on their role in promoting interactive communication and learner engagement. Results: The analysis reveals that mobile applications significantly enhance students’ communicative competence by providing interactive, flexible, and learner-centered environments. However, the study also identifies methodological, technical, pedagogical, and psychological challenges that limit optimal integration and emphasizes the need for more empirical research on this topic. Novelty: This article contributes to educational methodology by presenting a comprehensive analysis of mobile-assisted learning tools as facilitators of communicative competence, highlighting both their pedagogical value and the current research gap in technology-mediated language education.